Depression and Progression of Subclinical Cardiovascular Disease in Systemic Lupus Erythematosus. Issue 1 (21st November 2016) - Jorge, April; Lertratanakul, Apinya; Lee, Jungwha; Pearce, William; McPherson, David; Thompson, Trina; Barinas‐Mitchell, Emma; Ramsey‐Goldman, Rosalind
Abstract : Objective: Women with systemic lupus erythematosus (SLE) have an increased incidence of premature cardiovascular disease (CVD). A relationship between depression and increased inflammation leading to CVD has been proposed. The aim of this study was to evaluate the relationship between depression and the progression of subclinical atherosclerosis in women with SLE. Methods: In this prospective case–control study, 149 participants with SLE and 126 controls were followed over 5 years. Evaluation included laboratory studies, assessment of CVD risk factors, depression screening, ultrasound evaluations of carotid intima‐media thickness (CIMT) and carotid plaque, and assessment of SLE disease activity for the SLE cases. Results: The SLE group had a higher rate of depression: 29% compared with 11% in the control group ( P  = 0.003). When controlling for traditional CVD risk factors, the presence of baseline depression correlated with increased progression of CIMT in the SLE group, but not in the control group. The mean increase in CIMT was 0.026 mm in the SLE group without depression versus 0.064 mm in the depressed SLE group ( P  = 0.0096). There was no association between depression and carotid plaque in either group, with a calculated odds ratio for plaque progression in the depressed SLE group of 1.118 (95% confidence interval 0.476, 2.623) in the adjusted model. Conclusion: Women with SLE and concomitant depression have an increased risk of developing subclinical atherosclerosis, as measured by CIMT, but not by carotid plaque. The data suggest that depression, a potentially modifiable risk factor, may contribute to the increased risk of subclinical atherosclerosis in women with SLE.